2018
DOI: 10.1002/jcp.27938
|View full text |Cite
|
Sign up to set email alerts
|

EP2 and EP4 receptor antagonists: Impact on cytokine production and β2‐adrenergic receptor desensitization in human airway smooth muscle

Abstract: Prostaglandin E2 (PGE2) is a key prostanoid known to have both proinflammatory and anti‐inflammatory impact in the context of chronic respiratory diseases. We hypothesize that these opposing effects may be the result of different prostanoid E (EP) receptor‐mediated signaling pathways. In this study, we focus on two of the four EP receptors, EP2 and EP4, as they are known to induce cyclic adenosine monophosphate (cAMP)‐dependent signaling pathways. Using primary human airway smooth muscle (ASM) cells, we first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…We treated pericytes with specific inhibitors targeting EP receptors. We found that a cocktail of EP1/2/4 specific inhibitors [66][67][68][69][70][71] prior to PGE2 treatment allows pericytes to resume the morphology of untreated control cells (Fig. 4c) and intimately associate with ECs in 3-D coculture, thus restoring their capacity to form endothelial cords (Fig.…”
Section: Inhibition Of Ep Receptors Blocks the Effects Of Pge2 On Per...mentioning
confidence: 95%
“…We treated pericytes with specific inhibitors targeting EP receptors. We found that a cocktail of EP1/2/4 specific inhibitors [66][67][68][69][70][71] prior to PGE2 treatment allows pericytes to resume the morphology of untreated control cells (Fig. 4c) and intimately associate with ECs in 3-D coculture, thus restoring their capacity to form endothelial cords (Fig.…”
Section: Inhibition Of Ep Receptors Blocks the Effects Of Pge2 On Per...mentioning
confidence: 95%
“…The EP2 and EP4 receptors coupled to Gs activate adenylate cyclase (AC) and increase cAMP production, whereas the EP3 receptor inhibits cAMP signaling. EP receptors, selective agonists, or antagonists were used to amplify or antagonize PGE2 signal effects 15 - 18 . It's reported that solute carrier organic anion transporter family member 2A1 (SLCO2A1), known as prostaglandin transporter (PGT), is responsible for transporting extracellular PGE2 into the cell and performs a function in the intracellular activity of PGE2 13 , 19 .…”
Section: The Production and Downstream Signal Of Endogenous Pge2mentioning
confidence: 99%
“…The range of concentrations used in these studies are higher than that used in neuronal cultures (0.1–500 μM MPP+ and 10 nM-1 μM rotenone; Gao et al, 2003; Henze et al, 2005; Klintworth et al, 2009; Bournival et al, 2012; Jin et al, 2012; Du et al, 2014). Some authors have reported no alterations (Klintworth et al, 2009; Ferger et al, 2010; Jin et al, 2012), but others have shown the induction of pro-inflammatory markers in the MPP+- and rotenone-treated microglial cultures (Du et al, 2014; Zhang et al, 2014; Liang et al, 2015; Zhou et al, 2016). Differences in the pattern of neurotoxin treatment (concentration and duration of the treatment) and the cell types used (primary cultures and cell lines from different species) may partially account for the differences observed.…”
Section: Discussionmentioning
confidence: 96%
“…However, as MPP+- and rotenone-damaged neurons induce reactive microgliosis, which has a neurotoxic effect, it is difficult to establish the contribution of a direct effect of the toxins on glial cells in the neurotoxicity observed. In fact, although the neurotoxic effect of MPP+ and rotenone has been widely described using in vivo and in vitro experimental approaches, their direct effects on glial cells remain poorly characterized (Gao et al, 2003; Klintworth et al, 2009; Bournival et al, 2012; Du et al, 2014; Chen et al, 2015; Zhou et al, 2016). Most of the studies performed until now using glial cell cultures have tested whether these neurotoxins induce a pro-inflammatory phenotype in the microglial cells, and the results obtained are controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation